Influence Organizational Citizenship Behavior and Work Motivation on Job Performance of PT JNE Kota Kediri - Ria Lestari Pangastuti; Desi Kristanti (Jurnal Ekonomi & Bisnis JAGADITHA, 2021)
Organizations are systems and human activities that work together. In line with that, the organization is said to be a rational coordination of the activities of a number of people to achieve some general goals through the division of work and functions through a hierarchy of authority and responsibility. Analyzing the influence of motivation on job performance, analyzing the effect of job satisfaction on job performance, analyzing the influence of motivation on job satisfaction. This type of research is correlational analytic research. Correlation analysis is a statistical method used to measure the magnitude of the linear relationship between two or more variables. SEM, a complete modeling, basically consists of a measurement model (Measurement Model) and a Structural Model or Causal Model. This research is empirical evidence regarding the effect of motivation and OCB on achievement. This study uses a sample of 100 respondents who are employees of PT JNE Kota Kediri. The results showed that: motivation has an effect on OCB where effective motivation can increase or encourage an employee to feel satisfied, motivation has an effect on achievement. Where an employee who is committed to the organization will feel happy to be part of the organization, have trust and good feelings for the organization and have a desire to remain in the organization, and intend to do what is best for the organization.